Practical Position Tracking Control of a Robotic Manipulator Based on Fractional Order Sliding Mode Controller - Dumlu, Ahmet (Elektronika ir Elektrotechnika, 2018)
In this study, the practical position tracking control of a robotic manipulator has been performed using the proposed fractional-order sliding mode control scheme (FO-SMC). The designed control technique is composed by fractional calculus and sliding mode control (SMC) to guarantee the fast convergence of the joint positions to their desired values. The main idea behind the design of the FO-SMC control is that, the sliding mode control composed with fractional calculus contributes to reach a robust control performance of a nonlinear system in presence of uncertainties, disturbances and un-modelled dynamics without a complete dynamic model of the system. To validate and demonstrate the performance of FO-SMC method, an industrial robot manipulator with external load has been used in the real time experimental studies. The experimental outcomes demonstrate that the proposed fractional-order sliding mode control strategy has a better trajectory tracking performance in presence of the external payload for tracking tasks compared with the classical SMC. DOI: http://dx.doi.org/10.5755/j01.eie.24.5.21838